Space filling of β-cyclodextrin and β-cyclodextrin derivatives by volatile hydrophobic guests - Fourmentin, Sophie (Beilstein-Institut, 2013)
The inclusion of volatile derivatives of benzene and cyclohexane in β-cyclodextrin (β-CD), hydroxypropyl-β-CD, and hydrophilic β-CD-thioethers was investigated by static headspace gas chromatography (HS-GC) and molecular modelling. The obtained binding constants strongly increase with the amount of space filling of the CD cavity and the salt concentration. β-CD thioethers show a 3–10 times higher binding potential than native β-CD.